KESETARAAN DAN KESERASIAN GENDER DALAM AL-QURAN - Siti Alfiatun Hasanah; Lukman Hakim Husnan (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2022)
The narrative about gender justice is dominated by the notion of gender equality. In the interpretation of the Koran, this has serious implications, including forcing the application of the method of